The impact of the COVID-19 pandemic on vaccinations in United States primary care practices - Omer Atac; Lars E. Peterson; Teresa M. Waters (PLoS ONE, 2025)
Background The COVID-19 pandemic caused substantial burdens for patients and our healthcare delivery system. Many patients delayed seeking care for essential medical needs, and providers struggled to deliver services. This study aimed to examine the impact of the COVID-19 pandemic on administration of non-COVID-19 vaccinations through primary care practices, using a nationwide sample. Methods In this retrospective cross-sectional study, clinical records from the American Board of Family Medicine’s (ABFM) PRIME Registry for March 15, 2019 through March 14, 2022, were used to calculate monthly visit and vaccination rates among child-adolescents and adults, comparing Pre-Pandemic Year and Pandemic Years 1 and 2. Logistic regression was used to examine the association of patient characteristics with vaccination likelihood. Results The number of vaccinated individuals decreased by 9.6% among children-adolescents and 4.2% among adults in Pandemic Year 1. In the Pandemic Year 2, the decline had worsened as 19.4% for children-adolescents and 14.2% for adults compared to the Pre-Pandemic Year. Despite a partial rebound in visit rates, vaccination rates did not fully recover. Except few months, differences in vaccination rates were worse than those in visit rates throughout the rest of the pandemic. Females, rural residents and individuals living in areas with higher social risk had the lowest likelihood of vaccination and this gap increased during the pandemic. Conclusions The pandemic was associated with a decline in non-COVID-19 vaccinations that persisted through the second year of the pandemic. This decline raises concerns that delayed or missed vaccinations may trigger outbreaks of preventable diseases and the resurgence of diseases that were previously under control.